Anemia ferropénica y su relación con las complicaciones en gestantes durante el tercer trimestre, atendidas en el Hospital General Liborio Panchana Sotomayor. Periodo junio – octubre 2023. - Campos Cruz, Wendy Julissa (2023)
The research focuses on the relationship between iron-deficiency anemia and obstetric complications in pregnant women during the third trimester of gestation at General Liborio Panchana Sotomayor Hospital, between June and October 2023, such as preterm birth and low birth weight. The importance of iron intake in maternal and child health is emphasized, and risk factors are identified. Additionally, prevention and treatment strategies are reviewed. The research aims to provide evidence-based information to improve prenatal care and promote a healthy pregnancy, with implications at both the local and global levels.